Issues of Existing Pedagogy: Translanguaging as Resources to Enhance Learning at Basic Level in Nepal - Kadel, Purna Bahadur (Interdisciplinary Research in Education, 2021)
Nepal is a multilingual country. Classroom is a miniature of the society. Translanguaging pedagogy is being executed in English as a medium of instruction (EMI) setting in the classroom. This study attempts to investigate the existing pedagogical practices of non-language subjects and to explore the role and impact of translanguaging as resources to enhance learning of non-language subjects' viz. Science, Mathematics and Social Studies at basic level. This is a qualitative study in which phenomenological research design has been adopted to carry out this study. Twelve teachers and thirty students were selected to carry out this study. Semi-structured interview, focus group discussion, and classroom observation were used as tools to collect data. The findings of this study shows that learners' L1 is used as linguistic resources for knowledge construction; there is strong dominance of the ideology of English on them; translanguaging makes the learners involve in interactive classes; they develop critical and creative thinking skills and enhance motivation through translanguaging. It is concluded that mother tongues of the diverse learners could be very effective to be used as a means to understand the content knowledge of non-language subjects in the classroom.